How much imitation is there in a shadowing task? - Dufour, Sophie; Nguyen, Noel (Frontiers in Psychology, 2013)
Phonetic imitation, also called phonetic convergence, is currently at the heart of numerous investigations since it can inform us on both the nature of lexical representations and the link between production and perception processes in spoken language communication. A task that has been largely used to study phonetic imitation is the shadowing task, in which participants merely listen to and repeat isolated words. In this study, we examined the extent to which the phonetic convergence effect found when participants shadow auditory tokens, is an imitation of the speaker. We thus compared the phonetic convergence effect observed in a shadowing task to that observed when participants were explicitly instructed to imitate the productions they were exposed to. Although the phonetic convergence effect was greater when participants intentionally imitated the speaker's productions, shadowing and imitation instructions led to the same degree of convergence in a post-exposure task. Hence, the convergence effect found in a shadowing task and that found in an imitation task seem to share a general mechanism which is automatic and which taps into the long-term representations of the words in memory. At a more theoretical level, our results reinforce the claim that detailed auditory traces associated with perceived words are stored in memory and are later used for production.